King, Edward. Interview with Edward King, Perry's Cove. - Baccalieu Trail Heritage Corporation (2005)
This interview is part of a series of filmed oral histories, collected in 2005 by the Baccalieu Trail Heritage Corporation, from over 40 elders who grew up in the area. The Baccalieu Trail Heritage Corporation is a not-for-profit organization dedicated to preserving, promoting and protecting the heritage of the Baccalieu Trail Region. This project collected memories of living and working in the area, going to school, children’s games, home remedies, the first modes of transportation, supernatural beliefs, traditional industries and calendar customs and celebrations. This interview is with Edward King of Perry's Cove. The interviewer is Lori Power. The camera was operated by Julia Harrington and the interview was edited by Darrell Barrett.